2015
DOI: 10.3329/pa.v25i0.24070
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and opportunities of raw jute production: a household level analysis in Bangladesh

Abstract: The study was conducted to investigate the existing status and practices of jute cultivation. A total of 100 farmers were interviewed by using a structured interview schedule from two villages (Damor and Nathpara) of Kishoregonj sadar upazila of Kishoregonj district at their houses and/or farm sites during April to June 2014. The study confirmed that most farmers have improved their socio-economic conditions through jute cultivation. The impact analysis of jute cultivation on livelihood of jute farmers shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…were quite frequently detected and identified in geminated/rotted seeds in wet blotter paper. Same result was found by [41]. More intensive study about the role of two storage fungi Fusarium and Aspergillus on is required.…”
Section: Discussionsupporting
confidence: 59%
“…were quite frequently detected and identified in geminated/rotted seeds in wet blotter paper. Same result was found by [41]. More intensive study about the role of two storage fungi Fusarium and Aspergillus on is required.…”
Section: Discussionsupporting
confidence: 59%
“…Frequent association of Fusarium oxysporum with jute seeds and its demonstrated pathogenic potentiality of causing seed rot/germination failure and seedling blight to the crop, indicates that Fusarium oxysporum might also be a potential seed borne pathogen causing some diseases like wilt in the growing jute crop in the field [28]. Aspergillus species were quite frequently associated with the jute seeds and the fungi were also recorded in geminated/rotted seeds in wet blotter [29]. This indicates that the two storage fungi might affect the health of jute seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The highest output cost was found from T5 as 148421 Taka/ha which was statistically identical with other treatments except T1 (129261 Taka/ha). High input cost is a major constrain of jute production (Sheheli and Roy, 2014). During the experiment it was observed that input cost increased with the increasing of fertilizer amount.…”
Section: Yield Analysismentioning
confidence: 94%